Impact of halopriming on four wheat (Triticum aestivum L.) cultivars of balochistan under saline conditions - Buzdar, Summi; Mushtaq, Ayesha; Rizwan, Sabeena; Jabeen, Uzma; Bashir, Farrukh; Safdar, Farhat; Baloch, Mehnaz; Khan, Muzaffar; Razaq, M Aamir; Shahwani, Naeem (Bangladesh Journal of Botany, 2019)
Priming effect of silicon sources (silica gel and sodium silicate) on the seeds of four wheat cultivars of Balochistan was studied to determine their effectiveness in increasing relative salt tolerance. The study depicts that all priming treatments of silicon sources (except sodium silicate 2%) enhanced germination and reduced mean germination time (MGT) of seeds in comparison to the control i.e. hydropriming. After germination, the young seedlings were grown in hydroponics in Hoagland’s culture solution under controlled conditions in non-saline and saline (100 mM NaCl) environments. All the growth parameters (root and shoot length, fresh and dry weights of plants and chlorophyll content of leaves) severely reduced in hydroprimed seeds under saline environments, although increased by priming seeds with silicon sources. Thus silica compounds have potential effects to break the seed dormancy and improve the growth of wheat under salinity stress.